Species of Woody Plants in Green Open Spaces of Medan State University - Ritonga, Yusran Efendi; Harsono, Tri (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Universities play a critical role in the development of urban ecosystems, which include artificial forests, parks, and green open spaces. Medan State University is one of the campuses in Medan City, North Sumatra, that boasts a significant amount of green open space. In order to identify and prioritize the conservation of woody plant species, data collection is necessary. Methodology: The method employed exploration, which involves the recording of all woody plants and their presentation in a qualitative descriptive format. Findings: The data on woody plants in the green open spaces of Medan State University are categorized into 2 subdivisions, 48 families, and 146 species, as indicated by the study's findings. Contribution: Protective plants, medicinal plants, spices, fresh fruits, and ornamental plants are all utilized. It is anticipated that the findings of this investigation will serve as a reference for future research on woody plants in urban green open spaces